Hyperferritinemia in uncomplicated pediatric dengue patients in Kanchipuram, Tamil Nadu, India - S Mohammed Aashiq; Prahlad Kadambi; L Sushanth Prabath Reddy; Chithra S (Pediatric Review: International Journal of Pediatric Research, 2020)
Background: Dengue fever is an arboviral fever caused by 5 serotypes of Dengue Virus DENV1-5. Ferritin is an acute-phase reactant and produced by reticuloendothelial cells in response to inflammation and infection. Studies have shown that ferritin is a predictor of the severity of dengue. However, there are no studies correlating serum ferritin levels with the Dengue Antibody profile in pediatric patients in India.Aim: The objectives of this study were to assess serum ferritin levels in pediatric dengue patients, correlate it with the patient’s dengue antibody profile (Dengue IgM and IgG) and to correlate it with the hematological profile in pediatric dengue patients.Methodology: 58 Children who were admitted for fever of more than 3 days duration and Dengue NS1 antigen positive were included in the study. In these children; Total Count (TLC), Platelet Count (Plt), Hematocrit (PCV), Serum Ferritin levels were the investigative parameters measured at the time of admission for the purpose of the study. These patients were treated as per the WHO Dengue Guidelines. Data were coded and entered in Microsoft Excel 2013 and data was analyzed using SPSS v16. the p-value of <0.05 was considered to be statistically significant.Results: The mean age of the study population was 8.51±3.5 years. All 58 children had elevated serum ferritin levels. The mean serum ferritin levels in the study population as a whole were 8762.224±3556.09 µg/ml. The mean serum ferritin levels in children who were Dengue IgM negative was 7031.78±2669.44 µg/ml. There was a strong positive association between Serum Ferritin levels and Dengue IgM Status (r= 0.53, p=0.000029).Conclusions: Hyperferritinemia is seen in dengue fever and is associated with the Dengue IgM status of the child. There is a potential for serum ferritin levels to be used as a marker for diagnosis of dengue fever and in the prediction of the severity of dengue fever but needs to be confirmed in larger studies.